Thunderstorm Charge Distribution Determination Using Cosmic Rays Induced Air Showers and Lightning Imaging at LOFAR - Trinh, T. N.G.; Scholten, O.; van Loon, R.; Hare, B. M.; Assink, J. D.; Bouma, Sjoerd; Buitink, S.; Corstanje, A.; Cummer, S.; Desmet, M.; Dwyer, J.; Falcke, H.; et al. (Geophysical Research Letters, 2025)
The LOw Frequency ARray (LOFAR) radio telescope possesses the unique capability to measure ultra-high energy cosmic rays as well as image lightning discharges. This study presents a comparison between the inferred thunderstorm charge structures derived from cosmic-ray measurements and from lightning flashes. Our results show a basic triple-layered distribution: a positive upper layer, a main negative layer, and a positive lower layer. However, our cosmic-ray measurement shows a bottom-heavy structure, where the charge in the upper positively charged layer is smaller than that in the lower one. This is consistent with practically all lightning observations with LOFAR, showing well-developed negative leader structures at altitudes below those where positive leaders are seen. This is very different from the vast majority of thundercloud charge structures seen around the world.
CRIS-Team Scopus Importer:2025-05-16
Keywords: cosmic-ray air showers; lightning imaging; thunderstorm charge structures